Konsep Dasar Manajemen Tenaga Pendidik dan Kependidikan - Yulaekah, Yulaekah; Afriza, Afriza; Andriani, Tuti (Dinasti Review Publisher, 2023)
The management of teaching and educational staff is an activity that must be carried out starting from the teaching and education staff entering the educational organization until they finally stop going through the process of HR planning, recruitment, selection, placement, awarding of compensation, awards, development education and training and termination. The management of educational staff (teachers and staff) absolutely must be implemented by school principals in order to be able to utilize educational staff effectively and efficiently to achieve optimal results. In accordance with this, a school principal must be able to find, position, evaluate, direct, motivate, and develop the talents of each teacher and staff and be able to align individual and organizational goals.